Invading oysters and native mussels: from hostile takeover to compatible bedfellows. Issue 9 (15th September 2017) - Reise, Karsten; Buschbaum, Christian; Büttger, Heike; Wegner, Mathias K.
Abstract: Unintended species introductions may offer valuable insights into the functioning of species assemblages. A spectacular invasion of introduced Pacific oysters Magallana (formerly Crassostrea ) gigas in the northern Wadden Sea (eastern North Sea, NE Atlantic) has relegated resident mussels Mytilus edulis on their beds to subtenant status. At the beginning of feral oyster establishment, mussel beds offered suitable sites with ample substrate to settle upon. After larval attachment to mussels, the fast‐growing M. gigas overtopped and smothered their basibionts. With increasing Pacific oyster abundance and size, oyster larvae preferentially settled upon oysters, and the ecological impact of the invaders on the residents changed from competitive displacement to accommodation of mussels underneath a canopy of oysters. Oysters took the best feeding positions while mussels received shelter from predation and detrimental epibionts. The resident's mono‐dominance has turned into co‐dominance with an alien, persisting in novel, multi‐layered mixed reefs of oysters with mussels, which we term "oyssel reefs." The first 26 yr of the Pacific oyster's conquest of mussel beds in the northern Wadden Sea may question the overcome notions of natural balance, superiority of pristine over novel species combinations, and of introduced alien species threatening biodiversity and ecosystem stability in general.